The study of relationship between social capital and self-rated health in Bandar Abbas, Iran - Hedayat Allah Nikkhah (Social Determinants of Health, 2018)
Background: Health is a key component of an individual's welfare and the standard of living. Social capital has attained a considerable attention in science and policy making since researchers have suggested that it may have a positive impact on the well-being of individuals and the society. The aim of this study was to examine the relationship between social capital and self-rated health.